Prevalence, Clinical Severity, and Seasonality of Adenovirus 40/41, Astrovirus, Sapovirus, and Rotavirus Among Young Children With Moderate-to-Severe Diarrhea: Results From the Vaccine Impact on Diarrhea in Africa (VIDA) Study. (19th April 2023) - Keita, Adama Mamby; Doh, Sanogo; Sow, Samba O; Powell, Helen; Omore, Richard; Jahangir Hossain, M; Ogwel, Billy; Ochieng, John B; Jones, Joquina Chiquita M; Zaman, Syed M A; Awuor, Alex O; Juma, Jane; et al.
Abstract: Background: While rotavirus causes severe diarrheal disease in children aged <5 years, data on other viral causes in sub-Saharan Africa are limited. Methods: In the Vaccine Impact on Diarrhea in Africa study (2015–2018), we analyzed stool from children aged 0–59 months with moderate-to-severe diarrhea (MSD) and without diarrhea (controls) in Kenya, Mali, and The Gambia using quantitative polymerase chain reaction. We derived the attributable fraction (AFe) based on the association between MSD and the pathogen, accounting for other pathogens, site, and age. A pathogen was attributable if the AFe was ≥0.5. The severity of attributable MSD was defined by a modified Vesikari score (mVS). Monthly cases were plotted against temperature and rainfall to assess seasonality. Results: Among 4840 MSD cases, proportions attributed to rotavirus, adenovirus 40/41, astrovirus, and sapovirus were 12.6%, 2.7%, 2.9%, and 1.9%, respectively. Attributable rotavirus, adenovirus 40/41, and astrovirus MSD cases occurred at all sites, with mVS of 11, 10, and 7, respectively. MSD cases attributable to sapovirus occurred in Kenya, with mVS of 9. Astrovirus and adenovirus 40/41 peaked during the rainy season in The Gambia, while rotavirus peaked during the dry season in Mali and The Gambia. Conclusions: In sub-Saharan Africa, rotavirus was the most common cause of MSD; adenovirus 40/41, astrovirus, and sapovirus contributed to a lesser extent among children aged <5 years. Rotavirus- and adenovirus 40/41-attributable MSD were most severe. Seasonality varied by pathogen and location. Efforts to increase the coverage of rotavirus vaccines and to improve prevention and treatment for childhood diarrhea should continue. Abstract : Among children <5 years, rotavirus, adenovirus 40/41, and astrovirus cause moderate to severe diarrhea (MSD) in Kenya, Mali, and The Gambia, and sapovirus causes MSD in Kenya. Rotavirus and adenovirus 40/41 MSD have the highest severity.